Konsep Pendidikan Ibnu Miskawaih dalam Kitab Tahdzib Al-Akhlaq Wa Tathiir Al-A’raaq Dan Relevansinya Pada Pendidikan IPS di Sekolah Dasar - Fajrin, Laila; Siregar, Maragustam (J-PGMI: Jurnal Pendidikan Guru MI, 2024)
This study intends to examine the connection between elementary school social studies instruction and Ibn Miskawaih's conception of education as presented in the book Tahdzib Al-Akhlaq Wa Tathiir Al-A'raaq. Using a library research strategy, a qualitative research methodology is applied. Based on the data obtained, researchers discovered several of Ibn Miskawaih's educational concepts consisting of human concepts, soul concepts, moral concepts, educational goals and functions, educational materials and methods and educational environments. Researchers also present 5 stages in forming a child's character, namely natural, habit, training, punishment and praise. Apart from that, the researcher also explains the relevance of Ibn Miskawaih's Islamic education to social sciences. It is hoped that this research can contribute to providing an overview of the relevance of Ibn Miskawaih's education to learning carried out by educational institutions as well as providing ideas for academics who want to formulate the concept of Islamic education without ignoring general knowledge.